2007
DOI: 10.1523/jneurosci.3223-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Selective Visual Attention to Emotion

Abstract: Visual attention can be voluntarily directed toward stimuli and is attracted by stimuli that are emotionally significant. The present study explored the case when both processes coincide and attention is directed to emotional stimuli. Participants viewed a rapid and continuous stream of high-arousing erotica and mutilation stimuli as well as low-arousing control images. Each of the three stimulus categories served in separate runs as target or nontarget category. Event-related brain potential measures revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
421
9
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 499 publications
(496 citation statements)
references
References 55 publications
61
421
9
5
Order By: Relevance
“…Previous studies utilizing rapid picture presentations have found that emotionally significant stimuli consistently modulate both an early, as well as a late ERP component [1,3]. These results were replicated in the present study: pictures that were pleasant or unpleasant prompted greater EPN and LPP amplitudes compared to neutral pictures.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Previous studies utilizing rapid picture presentations have found that emotionally significant stimuli consistently modulate both an early, as well as a late ERP component [1,3]. These results were replicated in the present study: pictures that were pleasant or unpleasant prompted greater EPN and LPP amplitudes compared to neutral pictures.…”
Section: Discussionsupporting
confidence: 86%
“…The EPN elicited by the target picture was reduced when preceded by pleasant compared to neutral or unpleasant prime pictures, F(1, 24) = 55.0 and 61.7, p \ 0.001, which did not differ from each other, F(1, 24) = 0.1, ns. 3 Late Positive Potential (LPP) Figure 4 shows a representative centro-parietal sensor replicating enlarged LPP amplitudes to emotional prime pictures (upper panel). Of most interest, pleasant and unpleasant prime pictures reduced the LPP to the subsequent picture (target) irrespective of hedonic valence (middle panel).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the IAPS pictures used in our study did not include highly arousing pictures 683 (e.g., mutilations or erotica), for which gender differences might likely arise (Lithari et al, 2010;684 Proverbio et al, 2009;Schupp et al, 2007Schupp et al, , 2006. Moreover, future studies are needed to assess 685 whether the reported ERP effects may lead to differential long-term memory effects for 686 emotional compared to neutral scenes (Dolcos and Cabeza, 2002;Kaestner and Polich, 2011).…”
Section: Emotion-dependent Monotonic Accumulation Of Perceptual Evidementioning
confidence: 95%